2021
DOI: 10.3892/or.2021.8045
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of terrein on lung cancer cell metastasis and angiogenesis

Abstract: Cancer metastasis is the leading cause of mortality in cancer patients. Over 70% of lung cancer patients are diagnosed at advanced or metastatic stages, and this results in an increased incidence of mortality. Terrein is a secondary bioactive fungal metabolite isolated from Aspergillus terreus . Numerous studies have demonstrated that terrein has anticancer properties, but in the present study, the cellular mechanisms underlying the inhibition of lung cancer cell metastasis by terrein wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Compound 7 showed cytotoxicity against several cancer cells, with IC 50 values ranging from 2.6 to 12.9 µM. Terrein ( 14) displayed strong cytotoxicities against human breast cancer MCF-7 cells [38] and human lung cancer A 549 cells [39]. Hence, our findings were consistent with those reported in previous experiments, though different cancer cell lines were evaluated.…”
Section: Resultssupporting
confidence: 90%
“…Compound 7 showed cytotoxicity against several cancer cells, with IC 50 values ranging from 2.6 to 12.9 µM. Terrein ( 14) displayed strong cytotoxicities against human breast cancer MCF-7 cells [38] and human lung cancer A 549 cells [39]. Hence, our findings were consistent with those reported in previous experiments, though different cancer cell lines were evaluated.…”
Section: Resultssupporting
confidence: 90%
“…Terrein can simultaneously inhibit VEGF-A/VEGFR-2 and Integrin/focal adhesion kinase (Integrin/FAK) in A549 cells, in addition to reducing protein levels of downstream mediators, such as PI3K, AKT, mTORC1, and P70S6K, and expression of MMP-2 and MMP-9. Mechanically, Terrein inhibits the PI3K/AKT/mTOR signaling pathway by inhibiting HIF-1α and VEGF translation and angiogenesis in lung cancer ( 83 ). Similarly, studies have shown that fibrinogen α (FGA) can inhibit the proliferation, migration and angiogenesis of lung cancer cells by inhibiting the Integrin/AKT/mTOR signaling pathway, promoting cell apoptosis and exerting an anticancer role ( 84 ).…”
Section: Novel Anti-angiogenesis Strategies In Lung Cancer Treatmentmentioning
confidence: 99%
“…The effect of exogenous regucalcin on cancer cell adhesion was determined using Matrigel [44]. Briefly, 24-well plates were coated with 100 μL Matrigel Matrix (1:1 diluted in sterilized PBS, Corning) and incubated at 37°C for 2 h, and then the extra Matrigel was removed.…”
Section: Adhesion Assaymentioning
confidence: 99%